Femininities and Masculinities Depiction: A Critical Discourse Analysis - Farieda Ilhami Zulaikha (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2018)
Numerous studies offer proposal that women and men have their own way to convey a message. They share different characteristics in language production. This paper intends to reveal the language differences between women and men in writing a text. It analyzes students’ recount text writing, both women and men in the age of around 18 in a same theme. It encompasses qualitative and quantitative analysis drawn on Critical Discourse Analysis (CDA) of Fairclough (1989). It focuses on linguistic and cultural analysis. It follows three stages; description, interpretation, and explanation analyzing the lexical choice, content, and style of writing. It jumps to the result that women’s language is considered powerless and feminine, whether men’s language is powerful and masculine. It proves that language contains power relation and social status. Apparently, it reflects the patriarchal order, subordination and stereotype of women and men.